A administração pública em contexto de crise : uma análise da aplicação da gestão de riscos no enfrentamento às crises e mitigação de efeitos em políticas públicas - Costa, Igor Martins da (2024)
In a scenario of growing global, regional and local crises, such as the Covid-19 pandemic, society is facing significant impacts. Governments have reacted with emergency measures to mitigate the negative effects. However, government policies, programs and actions, in addition to facing planning and execution challenges, also suffer from these external factors, which impact on the allocation of resources and the effectiveness of objectives. The Public Administration must look after the common good, ensuring that public policies are effective and benefit citizens, acting preventively to avoid discontinuity and failure in their results. With the advent of New Public Management, the administration has been modernized, absorbing corporate management practices from the private sector to improve its governance. Risk management, an important pillar in this process, applied in the development and implementation of public policies, can minimize their interruptions or discontinuities. This research focuses on the application of risk management in dealing with crises and mitigating the effects of public policies within the Executive Branch of the state of Minas Gerais, with the aim of understanding the challenges to their development in the state. While risk management aims to assess and act on potential threats, crisis management deals with manifest risks or damaging events. The study employs an exploratory qualitative methodology, linking risk management and crisis management in the formulation of public policies, focusing on the experience during the Covid-19 pandemic in Minas Gerais. The work includes a literature review, documentary research and individual interviews. The empirical analysis focused on the selection of strategic projects carried out by the state's executive branch. It is crucial that organizations develop competencies to manage risks and crises at all levels, and this should be thought of both ex ante and ex post in public policy. Although Minas Gerais is making progress in these matters, the challenges for institutionalization are broad, ranging from awareness of the relevance to effective integration into strategic actions and decisions. It is necessary to strengthen current practices and foster a culture of risk management to deal with crises, ensuring better results and the well-being of the population.